The role of firm-level factors and regional innovation capabilities for Polish SMEs - Lukasz Arendt; Wojciech Grabowski (Journal of Entrepreneurship, Management and Innovation)
The paper elaborates on the innovativeness of Small and Medium-Sized Enterprises in Poland from the regional perspective. The empirical evidence is based on data collected among 820 Polish SMEs which actively use ICT tools in their business processes. Identifying firm-level (internal) and regional drivers of innovations in these enterprises was the main aim of this study. The originality of the utilized research approach lies in combining within one framework firm-level data with meso data describing the innovative potential of the regional environment and using multilevel random-effects models to analyze the relevance of firm-level and regional drivers of SMEs’ innovativeness. By deploying a regional random effects approach, we assessed indirectly the effectiveness of innovation policies conducted in Polish NUTS 2 regions within a RIS and S3 framework. Interestingly, the research hypothesis, stating that regional (external) factors are more important to enhance innovativeness of SME than firm-level (internal) drivers, was verified negatively. The study revealed that SMEs in less-developed regions of Poland rely more on in-house capabilities, than on the regional innovative potential, to introduce different types of innovations. This suggests that the S3 framework in less-developed regions should concentrate more on linking firm-level factors and regional innovation systems to enhance companies’ innovation capacity